1975
DOI: 10.1042/bj1490519
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of magnesium ions with teichoic acid

Abstract: The binding of Mg2+ to the wall teichoic acid of Lactobacillus buchneri N.C.I.B. 8007 was measured by equilibrium dialysis at controlled ionic concentration and pH. In an aqueous solution containing 10mM-NaCl at pH 5.0 one Mg2+ ion was bound for every two phosphate groups of the teichoic acid, with an apparent association constant, Kassoc. = 2.7 x 10(3) M-1. On lowering the pH below the pKa of the phosphate groups the amount of bound Mg2+ decreased concomitantly with decreasing ionization of the phosphate grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 20 publications
(32 reference statements)
6
60
1
1
Order By: Relevance
“…We could not detect fibronectin on HeLa cells with anti-fibronectin antibody (data not shown), suggesting that fibronectin plays little, if any, role in the binding of teichoic acid to HeLa cells. Teichoic acid also has an affinity with cations, especially magnesium (12,19), whereas the binding of teichoic acid to HeLa cells was not significantly affected by the magnesium or calcium concentration in the buffers (data not shown). From our results in this study, teichoic acid seems to bind almost specif- …”
Section: Discussionmentioning
confidence: 99%
“…We could not detect fibronectin on HeLa cells with anti-fibronectin antibody (data not shown), suggesting that fibronectin plays little, if any, role in the binding of teichoic acid to HeLa cells. Teichoic acid also has an affinity with cations, especially magnesium (12,19), whereas the binding of teichoic acid to HeLa cells was not significantly affected by the magnesium or calcium concentration in the buffers (data not shown). From our results in this study, teichoic acid seems to bind almost specif- …”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of these results in cation assimilation and binding has been the focus of some discussion (133,134,289,377). However, high affinity for divalent cations in the wall matrix would be counterproductive and thus would work against the corresponding cation transport system of the cell (e.g., the Mg 2ϩ transporter [348]).…”
Section: D-alanyl Esters In the Binding Of Ligandsmentioning
confidence: 99%
“…16A) (289). Further studies with WTA from S. aureus showed that the binding of Mg 2ϩ reflects the ratio of D-alanine to P (21,290).…”
Section: D-alanyl Esters In the Binding Of Ligandsmentioning
confidence: 99%
“…Other types of amphipathic polymers, such as lipomanna (17,18), choline phosphate-containing substance (Forssman antigen) (9), and fatty acid-containing heteropolysaccharide (20,23), were reported to be present, instead of typical lipoteichoic acids, in a limited number of gram-positive bacteria. The ubiquitous occurrence of such amphipathic polymers in a variety of gram-positive bacteria suggests their essential role in membrane functions (4,12). In 1984, Op den Camp et al (16) reported a new type of lipoteichoic acid, which consists of a polysaccharide chain (1,6-linked ,-D-glucan or 1,5-linked ,-D-galactofuranan), a 1,2-linked polyglycerophosphate chain, and a glycolipid moiety, in Bifidobacterium bifidum.…”
mentioning
confidence: 99%